Morbidity in users of Family Health teams in the northeast of Minas Gerais based on the International Classification of Primary Care - Valquiria M. Silva; Ivelisa V. S. Pereira; Maria de Jesus L. Rocha; Antônio P. Caldeira (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
This study aimed to characterize the profile of morbidity among users of family health teams in the northeastern macroregion of Minas Gerais, Brazil. This is a cross-sectional population-based study, developed with the teams of the Family Health Strategy (FHS). It was conducted by data collection, using semi-structured questionnaires with specific instruments adjusted for three categories of professional teams of the FHS: physicians, nurses and community health agents (CHA). We used the International Classification of Primary Care, second edition (ICPC-2) to encode morbidity. Information was collected from 17,988 people, and 10,855 (60.3%) were females; 1,662 (9.2%) questionnaires were related to care by the physician; 2,530 (14.1%) were related to care by nurses and 13,796 (76.7%) corresponded to visits by and meetings with the CHA. The main health problems were: circulatory diseases (especially hypertension), musculoskeletal problems (especially back pain) and diseases of the digestive tract (especially intestinal parasites), which accounted for more than 40% of the medical consultations. Nonspecific complaints and visits related to women's health were the most prevalent in the care by nurses. In meetings with CHA, complaints about respiratory, musculoskeletal and cardiovascular diseases were the most pointed. The morbidity profile observed does not differ substantially from the results of other studies. Small differences can be attributed to regional particularities.